Relationships between Wnt-Notch-Hippo signaling pathways and their relevance to colorectal cancer pathogenesis - Chai, Boon Lee (2018)
Colorectal cancer (CRC) is a heterogeneous disease caused by progressive accumulation of multiple genetic alterations. Aberrant Wnt, Notch and Hippo signaling pathways commonly observed in CRC contributes to the pathogenesis of the disease. Crosstalk between these signaling pathways has previously been studied separately, but the relationship between these three signaling pathways has yet to be fully elucidated. The objectives of this study are (1): to determine the abnormal biomolecule expression, and the possible relationship between Wnt, Notch and Hippo signaling pathways, and MSI status via immunohisto chemical staining, (2): to determine the relationship of reduced APC immunoreactivity and APC truncation mutations via mutational analysis, and (3): to associate MSI with mutations by targeted exome sequencing. Using Mann-Whitney U test, a significant difference between the CRC and apparently normal adjacent (ANA) tissue groups in immunohistochemical staining of cytoplasmic β-catenin, cytoplasmic APC, nuclear APC, p-GSK3β, DKK1, NICD1, Hes1, and cytoplasmic YAP was observed. Biomolecule expression was associated with various pathological parameters using 2 test. Cancer stage was significantly associated with expression of nuclear β-catenin (p=0.013), Notch1 (p=0.005), NICD1 (p=0.011) and nuclear YAP (p=0.001), histological grade was significantly associated with expression of cytoplasmic β-catenin (p=0.013), membranous β-catenin (p=0.020) and PMS2 (p=0.014). Tumour infiltration stage (T) was significantly associated with expression of cytoplasmic β-catenin (p<0.005), cytoplasmic APC (p=0.038), Notch1 (p=0.007) and NICD1 (p=0.006). Metastasis (M) stage was significantly associated with expression of nuclear β-catenin (p=0.049), and MSI was significantly associated with right sided tumour (p<0.005) and peritumoral lymphocytes aggregates (PLA) (p=0.032). Using Spearman’s rank test, novel correlation between Wnt, Notch and Hippo signaling pathways were discovered. Cytoplasmic β-catenin expression was negatively correlated with MSI status (p=0.002), p-GSK3β was positively correlated with FBXW7 (p=0.004), DKK1 was positively correlated with NICD1 (p=0.002), Hes1 (p=0.024) and nuclear YAP (p=0.019). NICD1 was positively correlated with cytoplasmic YAP (p=0.012), and Hes1 was positively correlated with nuclear YAP (p<0.005). Mutational analysis of APC gene discovered two novel mutations (p.H1349L and p.K1350fs*4) whereas targeted exome sequencing discovered EGFR mutation in Malaysian CRC populations besides other common mutations in CRC. In conclusion, nuclear β-catenin, Notch1 and NICD1 expression were discovered occurring at the early stage of CRC, while novel relationship between Wnt-Notch (DKK1-Hes1, DKK1-NICD1 and p-GSK3β-FBXW7), Wnt-Hippo (DKK1-NICD1) and Notch-Hippo (Hes1-nuclear YAP and NICD1-cytoplasmic YAP) signaling pathways were revealed in this study. This study also showed MSI was negatively correlated with cytoplasmic β-catenin expression.